The Censorship as a means of social control: an analysis from Boccaccio’s Decameron - Escamilla Martínez, Mario Iván (2024)
The enjoyment of human rights is fundamental for the development of human life. One of these rights is freedom of expression, which is affected by censorship; however, due to the principle of interdependence of human rights, censorship also violates cultural rights. In this text we will see the effects produced by the censorship of Boccaccio’s Decameron; starting from the scope of the violations of rights, the censorship process, and the content of the text, to the point of considering the law as an instrument of social control, through which groups of power can continue to exercise a hegemonic role over the population.